Law beyond Israel: from the Bible to the Qur'an - Zellentin, Holger Michael (Oxford Studies in the Abrahamic Religions Ser., 2022)
The Hebrew Bible formulates two sets of law: one for Israelites and one for gentiles living in the Holy Land. Law Beyond Israel argues that the laws for non-Israelites form the historical basis of qur'anic law, pointing to legal continuity from the Hebrew Bible to the New Testament and from late antique Christianity to nascent Islam.